2021
DOI: 10.2147/ijn.s323436
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficiency of Prodigiosins Conjugated with Selenium Nanoparticles in Rats Exposed to Chronic Unpredictable Mild Stress is Mediated Through Antioxidative, Anti-Inflammatory, Anti-Apoptotic, and Neuromodulatory Activities

Abstract: Purpose Depression is a mood disorder accompanied by intensive molecular and neurochemical alterations. Currently, available antidepressant therapies are not fully effective and are often accompanied by several adverse impacts. Accordingly, the ultimate goal of this investigation was to clarify the possible antidepressant effects of prodigiosins (PDGs) loaded with selenium nanoparticles (PDGs-SeNPs) in chronic unpredictable mild stress (CUMS)-induced depression-like behavior in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 107 publications
2
6
0
Order By: Relevance
“…Accumulating evidence has strongly suggested that changes in monoaminergic, amino acidergic, and cholinergic transmission play crucial roles in regulating epileptogenesis [17,20]. In line with previous reports, the current study identified marked decreases in the levels of 5-HT and its metabolite (5-HIAA), DA, and NE and reduced AChE activity in PTZ-injected rats, which was accompanied by apparent increases in the DOPAC and HVA levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Accumulating evidence has strongly suggested that changes in monoaminergic, amino acidergic, and cholinergic transmission play crucial roles in regulating epileptogenesis [17,20]. In line with previous reports, the current study identified marked decreases in the levels of 5-HT and its metabolite (5-HIAA), DA, and NE and reduced AChE activity in PTZ-injected rats, which was accompanied by apparent increases in the DOPAC and HVA levels.…”
Section: Discussionsupporting
confidence: 90%
“…The developed powder was used in the current investigation. Our recent report showed that the obtained nanoformulation (SeNPs-PDG) are characterized with 109.3 average diameters and −13.9 mV as a mean zeta potential record [17]. In addition, TEM analysis revealed that the size of the developed nanoformulation is smaller than 200 nm (Figure S1).…”
Section: Chemicalsmentioning
confidence: 91%
“…Ice water swimming: a container with a depth higher than the rat’s body length, and 4 °C ice water was filled in the container up to the height of the rat’s neck (Albrakati et al. 2021 ). Rats in the normal control group had free access to food and water and were not subjected to any stress.…”
Section: Methodsmentioning
confidence: 99%
“…33 In recent years, the role of Se NPs in neurodegenerative diseases has been extensively studied and confirmed. 34,35 Therefore, in this context, we processed rutin into selenium-rutin nanoparticles (Se-Rutin) to solve the problem of low bioavailability of rutin and further enhance the anti-oxidation effects. The results demonstrate that Se-rutin significantly alleviates the oxidative stress-induced cell damage and apoptosis by activating Nrf2/HO-1 signal pathway in rat pheochromocytoma (PC12) cells.…”
Section: àmentioning
confidence: 99%